Micro credit marketing strategies in the post war marketing context. - Shivany, S.; Velnampy, T.; Kajendra, K. (University of Jaffna, 2014)
Absence of research on micro credit marketing strategies which significantly contributing factor to strategic marketing, and micro credit marketing in the financial and nonprofit organizations domain, and the extant research on marketing strategies lacks in theory based frameworks that explicate what marketing strategies are appropriate for micro credit marketing in the post war marketing context. Present study explored marketing strategies for micro credit in the unique context. Using grounded theory approach, data were collected from 08 focus group discussions, and in depth interviews with different micro credit marketing organizations. This study compared the profit oriented micro credit organizations and nonprofit organizations. NVivo (version 09) software was used to manage the focus group data. Transcripts were reviewed as the data collection to identify emerging ideas and specific themes, which guided subsequent data collection efforts. To code the data, open coding and axial coding schemes were used. market orientation, ethical marketing, post war development as differentiation, Customer service in good relation, Participation in group-lending have been identified as the marketing strategies which have been adopted by the profit and nonprofit orientated organizations in the post conflict marketing context.
Keywords: Micro credit marketing; Marketing strategies; Postwar context; Grounded theory